Factors affecting the access to health services among waste collectors in Hanoi, Vietnam: A qualitative study - Pham Tien Nam; Nguyen Hanh Dung; Nguyen Kim Oanh; Ha Thi Thu (AIMS Press, 2020)
Background: Waste collection is a common practice in Vietnam. In general, the working and living conditions of waste collectors are poor. Thus, they might be exposed to occupational and environmental risk factors, which affect their health or could further exacerbate their health vulnerabilities. Moreover, they have difficulties to access to health services. Objective: The aim of this study was to understand factors affecting the access to health services among waste collectors in Hanoi, Vietnam. Methods: The qualitative design was used for this study. A total of 30 in-depth interviews with waste collectors and 3 focused group discussions were conducted in Hanoi, Vietnam in 2017. Results: Findings showed the participants considered factors that affect the access to health services among waste collectors such as geographical accessibility, the availability of health facilities, the acceptance of the quality of health services, health insurance, and affordability. Conclusions: Policy makers concerned with public health and social work need to have the suitable policies in order to promote actions on the access to health services among waste collectors.